Presencia de Phomopsis viticola (Saccardo) Saccardo, agente causal de excoriosis, en viñedos de Cordoba, Argentina - Cragnolini, C.I.=700 1 March, G.J.; Viglianco, A.I.; Novo, R.J.; Bugiani, R.; Barreto, D.
(Es, En)
Ilus., 25 ref.
Keywords: VITIS VINIFERA; VITIS LABRUSCA; PHOMOPSIS; NECROSIS; MORBOSIDAD; ARGENTINA; VIÑEDOS; AGRISCIENTIA